2014
DOI: 10.1111/hsc.12092
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the home‐care and healthcare service use and costs of older A ustralians randomised to receive a restorative or a conventional home‐care service

Abstract: Restorative home-care services, or re-ablement home-care services as they are now known in the UK, aim to assist older individuals who are experiencing difficulties in everyday living to optimise their functioning and reduce their need for ongoing home care. Until recently, the effectiveness of restorative home-care services had only been investigated in terms of singular outcomes such as length of home-care episode, admission to hospital and quality of life. This paper reports on a more complex and perhaps mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
88
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(93 citation statements)
references
References 6 publications
(13 reference statements)
0
88
0
5
Order By: Relevance
“…As a potential result of the diverse conceptualisations and applications of reablement, previous studies have shown contradicting research findings. While several studies underline that the effectiveness of reablement is uncertain and there is a need for more thorough research (Aspinal et al, ; Cochrane et al, ; Legg et al, ; Whitehead, Worthington, Parry, Walker, & Drummond, ), other studies have shown beneficial effects of reablement related to, for instance, daily functioning or activity performance (Langeland et al, ; Lewin & Vandermeulen, ; Tuntland, Aaslund, Espehaug, Førland, & Kjeken, ; Winkel, Langberg, & Wæhrens, ) and healthcare use or costs (King, Parsons, Robinson, & Jorgensen, ; Lewin, Alfonso, & Alan, ; Lewin, De San Miguel, et al, , Lewin et al, ; Parsons et al, ; Tessier, Beaulieu, McGinn, & Latulippe, ). However, only a few studies were conducted to get insight into the experiences of home‐care workers.…”
Section: Introductionmentioning
confidence: 99%
“…As a potential result of the diverse conceptualisations and applications of reablement, previous studies have shown contradicting research findings. While several studies underline that the effectiveness of reablement is uncertain and there is a need for more thorough research (Aspinal et al, ; Cochrane et al, ; Legg et al, ; Whitehead, Worthington, Parry, Walker, & Drummond, ), other studies have shown beneficial effects of reablement related to, for instance, daily functioning or activity performance (Langeland et al, ; Lewin & Vandermeulen, ; Tuntland, Aaslund, Espehaug, Førland, & Kjeken, ; Winkel, Langberg, & Wæhrens, ) and healthcare use or costs (King, Parsons, Robinson, & Jorgensen, ; Lewin, Alfonso, & Alan, ; Lewin, De San Miguel, et al, , Lewin et al, ; Parsons et al, ; Tessier, Beaulieu, McGinn, & Latulippe, ). However, only a few studies were conducted to get insight into the experiences of home‐care workers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out in England, Australia, and Norway confirm that HCR is able to achieve positive independence outcomes (Glendinning et al, ; Lewin et al, ; Lewin & Vandermeulen, ; Tuntland, Aaslund, Espehaug, Førland, & Kjeken, ; Whitehead, Worthington, Parry, Walker, & Drummond, ). In particular it has been found to decrease dependency, as measured in terms of activities of daily living scores (Whitehead et al, ) and to increase self‐perceived activity performance and satisfaction with performance (Tuntland et al, ).…”
Section: Introductionmentioning
confidence: 95%
“…In the absence of clear evidence on health outcomes, the question whether HCR can lead to cost savings is an important question given the expectation of policy makers in England in this regard. Lewin et al (, ) found in their evaluation of HCR in Australia that over a 2‐year period aggregated hospital and home care costs in the intervention group (reablement) were between AU$2,869 and AU$4,338 lower than in the control group. This finding referred specifically to people who required personal care (rather than other types of home care).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity (PA) interventions are not included in these services despite the known functional and physical benefits of these interventions (American College of Sports Medicine [ACSM] et al, 2009). Specific to the population of older adults receiving reablement, or restorative home care services from a personal care attendant, exercise can have measurable cost savings, as well as physical health benefits for older adults (Lewin et al, 2014). Reablement services in the United Kingdom and Australia have integrated wellness approaches into the line of services; however, this model has not been commonly adopted in the United States at this point.…”
Section: Introductionmentioning
confidence: 99%